PENGARUH LATIHAN INTERVAL TRAINING TERHADAP DAYA TAHAN PARU DAN JANTUNG PADA TIM BASKET PUTRA SMKN 7 PEKANBARU - Darmawan, Budi; ', Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this study is the lack of endurance at the time of two-point shots during training and at O2SN tournaments conducted in school and o2sn field in the basketball senapelan. Based on these problems the researcher gives interval training training. This study aims to determine whether there is an effect of training interval training on the endurance of the lungs and heart on the men's basketball team SMKN 7 Pekanbaru, so that when the first quarter and second physical condition of the player is still excellent, enter the third quarter and the fourth player often exchange players and visible Also the player is very tired. The form of this research is experimental (experimental) research, with population of men's basketball team SMKN 7 Pekanbaru, the data in this study is the entire population of 12 people. The instrument performed in this study is a 400 meter run, which aims to measure respiratory durability (cardiovascular). After that, the data were processed with statistics, to test the normality by lilifors test at a significant level of α (0.05). The hypothesis proposed is the effect of training interval training on the endurance of lung and heart. Based on the statistical data analysis, there is an average pree-test of 29.53 and the post-test average of 32.79, then the data is normal with an increase of 3.49. Based on t test analysis yielded Thitung equal to 2,251 and Ttabel 1,895, mean Thitung> T table. Thus, there is the Effect of Interval Training Training Against Lung and Heart Resistance at Basketball Team of SMKN 7 Pekanbaru.Keywords: Interval Training, endurance of lungs and heart